Diagnostic accuracy of point of care faecal immunochemical testing using a portable high‐speed quantitative analyser for diagnosis in 2‐week wait patients. (16th July 2021) - Maclean, William; Mackenzie, Paul; Limb, Chris; Zahoor, Zahida; Whyte, Martin B.; Rockall, Timothy; Benton, Sally C.; Jourdan, Iain
Abstract: Aim: Laboratory‐based faecal immunochemical testing (FIT) is the gold standard for detecting the presence of blood in the stool. The aim was to perform a diagnostic accuracy study to confirm if a point of care (POC) analyser for FIT could be safely used as an adjunct in the triage and management of 2‐week wait (TWW) colorectal patients. Methods: The Point of Care Faecal Immunochemical Testing (POC FIT) prospective observational cohort study was designed for TWW patients at a regional referral centre. Between July 2019 and March 2020, patients were invited to perform and bring a FIT sample to clinic. FIT was completed within the clinic appointment using a POC quantitative analyser that has a 2‐min processing time (QuikRead go®). Patients and clinicians were blinded to results within the clinic appointment. The results were compared with subsequent diagnostic outcomes. Faecal haemoglobin of <10 µg haemoglobin/g of faeces was considered a negative result. Sensitivities for colorectal cancer (CRC) and combined serious bowel disease (SBD) were calculated using this pre‐determined cut‐off. Results: A total of 553 patients were included for analytical comparison with diagnostic outcomes. There were 14 (2.5%) patients with CRC and 52 (9.4%) with SBD. The sensitivities for CRC and SBD were 92.9% (95% CI 68.5%–98.7%) and 76.9% (95% CI 63.9%–86.3%) respectively. 379 (68.5%) patients had a negative FIT result (negative predictive value for CRC was 99.7%). Conclusions: This POC FIT device is a useful adjunct to better manage TWW patients. The high observed sensitivity for CRC offers opportunities, within a single consultation, for improved triage and rationalization of investigation for those with bowel symptoms.